ANALISIS PERMINTAAN KAYU LAPIS DI JAWA - Satria Astana; Buharman Buharman (Jurnal Penelitian Hasil Hutan, 1986)
One of  the main  important things for  the planning  of production and marketing  development is the demand informations. This research was conducted to analyse the aggregate demand  of plywood  in the districts of Java and its determining  factors.  The result of this research revealed that the aggregate demand  of plywood  in the districts of Java ranged from 679. 731 m3 to 1741.841  m3. The number of people  and the gross domestic regional income in the districts determine  the aggregate demand  of plywood significantly.  The elasticity  of the number of people  is 0.12  and the gross domestic  regional income  is 0.16. In addition,  this research found  that the distribution  of its consumption  consisted  of 60. 02% of the households,  25.22%  of the building contractors,  10.97%  of the furniture  craft industries and  3. 79% of the car body craft industries.